Clinical practice guideline recommendations for pediatric injury care: protocol for a systematic review. Issue 4 (27th April 2022) - Moore, Lynne; Freire, Gabrielle; Ben Abdeljelil, Anis; Berube, Melanie; Tardif, Pier-Alexandre; Gnanvi, Eunice; Stelfox, Henry Thomas; Beaudin, Marianne; Carsen, Sasha; Stang, Antonia; Beno, Suzanne; Weiss, Matthew; et al.
Abstract : Introduction: Evidence suggests the presence of deficiencies in the quality of care provided to up to half of all paediatric trauma patients in Canada, the USA and Australia. Lack of adherence to evidence-based recommendations may be driven by lack of knowledge of clinical practice guidelines (CPGs), heterogeneity in recommendations or concerns about their quality. We aim to systematically review CPG recommendations for paediatric injury care and appraise their quality. Methods and analysis: We will identify CPG recommendations through a comprehensive search strategy including Medical Literature Analysis and Retrieval System Online, Excerpta Medica dataBASE, Cochrane library, Web of Science, ClinicalTrials and websites of organisations publishing recommendations on paediatric injury care. We will consider CPGs including at least one recommendation targeting paediatric injury populations on any diagnostic or therapeutic intervention from the acute phase of care with any comparator developed in high-income countries in the last 15 years (January 2007 to a maximum of 6 months prior to submission). Pairs of reviewers will independently screen titles, abstracts and full text of eligible articles, extract data and evaluate the quality of CPGs and their recommendations using Appraisal of Guidelines Research and Evaluation (AGREE) II and AGREE Recommendations Excellence instruments, respectively. We will synthesise evidence on recommendations using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) Evidence-to-Decision framework and present results within a recommendations matrix. Ethics and dissemination: Ethics approval is not a requirement as this study is based on available published data. The results of this systematic review will be published in a peer-reviewed journal, presented at international scientific meetings and distributed to healthcare providers. PROSPERO registration number: International Prospective Register of Systematic Reviews (CRD42021226934).